INTELLECTUAL CAPITAL DISCLOSURE (ICD): A COMPARISON BETWEEN INDONESIAN AND CHINESE UNIVERSITIES - Aviani Widyastuti; Siska Aprillia (Universitas Muhammadiyah Malang, 2019)
The purpose of this study was to identify the practice of disclosure of information on intellectual capital on the website of the university in Indonesia and China. This research uses website the 10 best universities in Indonesia and China (version 4ICU survey 2018) as an object of study. Intellectual capital components used in this study is a framework developed by Leitner (2004) which consists of 36 items: 10 items of human capital, structural capital of 11 items, and 15 items of relational capital. The analysis used is content analysis, the different test performed using the Mann-Whitney test in SPSS. The results showed that there was no difference between the best universities in Indonesia and China to disclose information on intellectual capital through their website. In general, the number of IC disclosures through the best universities in Indonesia and China was around 45%, the rest is not disclosed.